Aplicación De La Nic 2, En El Proceso Contable Y Su Incidencia En Los Estados Financiero De Almacenes Lorences. - Arreaga Ortega, Maria de Lourdes (2017)
The present case study entitled "Application of La Nic 2, in the Accounting Process and Its Incidence in the Financial Statements of Lorences Warehouses" is intended to identify the problems that exist in this store in the accounting field, especially in regarding inventory control. The inventories are tangible goods, goods or articles that the entity owns and then sell them, these constitute the largest existing asset in Almacenes Lorences. Inventories are of great importance for this you have to take control, without making exceptions by the type of business or its size, although sometimes it is not easy task, but also not impossible, since the control of the inventories will allow to carry an adequate organization that would improve the profitability of the organization. Companies that are engaged in the purchase and sale of goods, constantly need summarized and analyzed information on their inventories, in accounting management this will allow the entity to maintain control in a timely manner, and also to know at the end of the accounting period a reliable result that allows to measure the real financial situation of the economic entity. In the development of the case study was determined by the applied research techniques that were the direct observation and interview, in the warehouse there is a poor management, valuation and control of inventories, and this is affecting the financial statements, since the information they present is not reliable for decision making